2003
DOI: 10.1093/aob/mcg176
|View full text |Cite
|
Sign up to set email alerts
|

Day and Night Temperature Responses in Arabidopsis: Effects on Gibberellin and Auxin Content, Cell Size, Morphology and Flowering Time

Abstract: The effect of 16 different day (DT) and night (NT) temperature combinations (DT and NT 12, 17, 22 and 27 degrees C) on rosette leaf growth, flower stem elongation and flowering time in Arabidopsis thaliana Ler was investigated. Final leaf length decreased with increasing NT due to a combination of reduced elongation period and reduced elongation rate. Final stem length increased with increasing DT due to increased elongation rate, and decreased with increasing NT due to a decrease in elongation period. Under N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 30 publications
4
57
0
Order By: Relevance
“…Does the environment regulate FT function as well? Low ambient temperatures delay flowering time of Arabidopsis plants (Blazquez et al, 2003;Thingnaes et al, 2003). Here, we show that low temperatures reduce the function of FT/TFT.…”
Section: Ft Function Is Reduced At Low Ambient Temperaturesmentioning
confidence: 58%
“…Does the environment regulate FT function as well? Low ambient temperatures delay flowering time of Arabidopsis plants (Blazquez et al, 2003;Thingnaes et al, 2003). Here, we show that low temperatures reduce the function of FT/TFT.…”
Section: Ft Function Is Reduced At Low Ambient Temperaturesmentioning
confidence: 58%
“…Moreover, the difference between daytime and nighttime temperatures may influence the levels of endogenous gibberellin (Thingnaes et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the study by Erwin et al (1994), it was indicated that the stem elongation of L. longiflorum developed at positive DIF was due to only longer but not more cells than at negative DIF. But Thingnaes et al (2003) also found that the elongation and division of stem cells in A. thaliana were both affected by DIFs. The section samples were chosen only from the middle part of the plant stems in this presented study, which could show an approximate estimate for the entire stem of flax.…”
Section: Discussionmentioning
confidence: 96%
“…From the cellular studies, stems developed under positive DIF have longer cells than under negative DIF, and transverse and longitudinal directions of cell expansions in Arabidopsis thaliana were affected by alternating day and night temperature (Thingnaes et al, 2003). In Lilium longiflorum, Erwin et al (1994) found that stem parenchyma, stem and leaf epidermal cell length were found to increase as the difference (DIF) between DT and NT increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation